Function‐integrated network for flying‐capacitor three‐level DC–DC conversion system. Issue 9 (4th April 2016) - Chen, Yu; Zhong, Zhihao; Kang, Yong
Abstract : Flying‐capacitor (FC) three‐level (TL) DC–DC topology is an attractive candidate for the switching‐mode power supply due to its low‐voltage stresses on semiconductors, small size of filter and common‐ground feature. However, to avoid the semiconductors to be damaged from an initial high voltage, the FC must be precharged to half of the input voltage by a bulky precharger. An idea to realise the precharging function by adding only one switch and cooperating it with the existent circuits is proposed. In this way, the necessary soft‐starting circuit and Resistor‐Capacitor‐Diode (RCD) snubbers for reliability purpose can be fully utilised to precharge the FC. Merits of the proposed idea include the lower cost, the more compact structure and the higher overall efficiency. The principles of the proposed function‐integrated network are analysed, and a 1.2 kW FC‐TL conversion system is also built to verify the analysis.